Spiral Dynamics of the Development of the Process of Intellectualization in the Context of Globalization Changes: Methodological Aspects - Shepelenko Svitlana M. (Problemi Ekonomiki)
The aim of the article is to study the methodological aspects of the spiral dynamics of the development of the process of intellectualization in the context of globalization changes. The article discusses the features of the development of the process of intellectualization in the context of globalization changes through the prism of the theory of spiral dynamics. Spiral dynamics, as a conceptual model of the evolution of human consciousness, allows us to analyze the transformations of society at different stages of its development. The influence of globalization factors on the processes of intellectualization is studied, emphasizing the role of information technology, network society and knowledge economy. The article allocates that the synergetic evolution of human potential is based on different phases of order (stability – homeostasis) or chaos (crisis, danger) under the influence of endogenous and exogenous environment. The analysis of literary sources provided an opportunity to form a methodology for managing the intellectual potential of enterprises in the context of global transformations. The paper focuses on the interaction between different levels of consciousness that determine the evolutionary movement of society, and shows how these interactions form new paradigms of thinking and activity. Also, the challenges and opportunities that arise in the process of intellectualization are considered, strategic approaches to change management based on spiral dynamics are proposed. The results of the study can be useful for scientists, politicians and managers involved in the development of society in the context of globalization.